In-depth structural proteomics integrating mass spectrometry and polyacrylamide gel electrophoresis - Takemori, Nobuaki; Takemori, Ayako (Frontiers in Analytical Science, 2023)
The establishment of a highly sensitive method for obtaining structural information on proteins and protein complexes in vivo has long been a technological challenge in structural biology. In recent years, protein structure analysis approaches using top-down mass spectrometry, native mass spectrometry, and cross-linking mass spectrometry, among others, have been developed, and these techniques have emerged as the most promising methods for obtaining comprehensive structural information on the cellular proteome. However, information obtained by MS alone is derived mainly from protein components that are abundant in vivo, with insufficient data on low abundance components. For the detection of those low abundance components, sample fractionation prior to mass spectrometry is highly effective because it can reduce the complexity of the sample. Polyacrylamide gel electrophoresis (PAGE), which is widely used in biochemical experiments, is an excellent technique for protein separation in a simple straightforward procedure and is also a promising fractionation tool for structural proteomics. The difficulty of recovering proteins in gels has been an obstacle, thus far limiting its application to structural mass spectrometry. With the breakthrough of PEPPI-MS, an exceptionally efficient passive extraction method for proteins in gels that appeared in 2020, various PAGE-based proteome fractionation workflows have been developed, resulting in the rapid integration of structural mass spectrometry and PAGE. In this paper, we describe a simple and inexpensive PAGE-based sample preparation strategy that accelerates the broad use of structural mass spectrometry in life science research, and discuss future prospects for achieving in-depth structural proteomics using PAGE.